Hydraulic modelling and validation for the study of smolt migration - Kiviloog, Jaan; Bergdahl, Lars; Rivinoja, Peter; Leonardsson, K; Lundquist, Hans (2004)
In order to assess the prerequisites for downstream migration of smolt the flow field upstream two hydropower stations in two large Swedish rivers have been made, and the simulations have been validated against stream velocities measured on site. The validated models have been used to compare the flow paths with the measured swimming paths of smolts. The simulations were done by solving the three dimensional Reynolds-averaged Navier-Stokes equations using the Fluent computational fluid dynamics (CFD) package. One of the studied rivers, Ume älv, whose main course is completely regulated, has a large unregulated tributary river, Vindelälven, which holds important spawning grounds for salmon (Salmo salar) and trout (Salmo trutta), and downstream of the confluence of the two rivers there is only one hydropower plant, the Stornorrfors power plant. This constitutes a major hindrance for fish migrating between the Bothnian Sea and the spawning grounds of the river Vindelälven. The juvenile fish, smolt, leaving the Vindelälven downstream towards the ocean can migrate either through the turbines and deep rock tunnels of the power plant or through the surface weirs at the regulating dam. Because of the flow regime during the migration period of smolts most smolts are believed to follow the main stream through the turbines leading to a mortality of approximately 25 %. The other studied river, Pite älv, also contain some spawning grounds in smaller tributaries upstream its first power plant. Although this plant is more like a-run-of-the-river plant most smolt passes the turbines instead of going over the spillways.The objective of the study is to determine the migration paths of salmon and trout smolts and relate their behaviour to hydraulic factors. The results from the study could then be used to improve smolt survival by taking appropriate measures to divert the smolts from the turbines, e.g. by changing spill rules or installing diversion systems.In Ume älv in Spring 2002, 22 salmon and 22 trout smolts were tagged with ...